Aspectos limnológicos da pequena açudagem no semiárido: estudo de caso dos açudes do Assentamento 25 de Maio, Madalena-Ce - Feitosa, Leonardo Schramm (2011)
The studies for small reservoirs in the semiarid northeast are still scarce, mainly in relation to water quality. This research aimed to discover the dynamic processes that occur in small reservoirs, to evaluate the multiple uses, the trophic state and water quality in small reservoirs representing the settlement on May 25. Carried out the systematic monitoring of water quality of the reservoirs Paus Branco and Mel, in the period April 2010 to October 2010. The variables analyzed were: temperature, transparency, euphotic zone, pH, turbidity, conductivity, total phosphorus, soluble orthophosphate, N-ammonia, nitrite, nitrate, total nitrogen, total solids, chlorophyll-a, COD, BOD5,20 and thermotolerant coliforms. The small reservoir benefits the population of the settlement on May 25 on supplies of the population, to fish farming, cultivation of low water and irrigation. Human activities with the greatest impact on water quality in two reservoirs monitored, restricted: animal husbandry and the its presence on the banks of reservoirs, cultivation of low water, the use of pesticides by the settlers, the landfill waste or its outdoor presence, dumping of waste water for household chores in the yard and the deforestation of riparian forests of the reservoirs. There was significant difference between the wet and dry periods, the following parameters: temperature, pH, PT, NT, N-ammonia, nitrite, nitrate, BOD, DO, chlorophyll a and thermotolerant coliforms. The trophic state index of Lamparelli (2004) indicates that the reservoirs Paus Branco and Mel may be eutrophic in all their points, because they have the classifications: eutrophic, to the reservoir Paus Branco, and between supereutrófico and hypereutrophic, to the reservoir Mel. The high values obtained in the N:P ratios give an indication that phosphorus is the limiting nutrient in the two reservoirs. N:P ratios higher in the dry period than during the rainfall period may be due to sedimentation or the assimilation of phosphorus by algae and aquatic plants. The systematic monitoring in the model used in this study, with monthly sampling at three points of each reservoir, obtaining samples from the limnetic zone, collected in two periods, rainfall and dry periods, was successful, providing information on the reservoirs and their watersheds. The results corroborate other finding results of the semiarid northeastern reservoirs and reinforce the hypothesis that seasonal variations affect water quality in reservoirs.